2011
DOI: 10.1002/alr.20046
|View full text |Cite
|
Sign up to set email alerts
|

Increased presence of dendritic cells and dendritic cell chemokines in the sinus mucosa of chronic rhinosinusitis with nasal polyps and allergic fungal rhinosinusitis

Abstract: AFRS and CRSwNP have increased numbers of DCs displaying costimulatory molecules, DC chemoattractants, and their corresponding receptors in the sinus mucosa compared to controls. These differences represent a possible mechanism for increased numbers of DCs with a T helper 2 (Th2)-skewed profile seen in CRSwNP and AFRS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 38 publications
3
37
0
Order By: Relevance
“…In contrast, the numbers of IL-13, but not IL-4, mRNA-positive cells were increased in the CRS subjects without atopic symptoms compared with the normal controls. Results of these investigations suggest that the relationship between the two cytokines IL-4/IL-13 and the polyp formation is not necessarily associated with the induction of eosinophilic inflammation (al Ghamdi et al, 1997;Ayers et al, 2011;Bhakta and Woodruff, 2011). In our study, similarly to POSTN, we found that the IL-13 expression level was markedly higher in the NP tissues compared with the adjacent mucosa.…”
Section: Discussionsupporting
confidence: 54%
“…In contrast, the numbers of IL-13, but not IL-4, mRNA-positive cells were increased in the CRS subjects without atopic symptoms compared with the normal controls. Results of these investigations suggest that the relationship between the two cytokines IL-4/IL-13 and the polyp formation is not necessarily associated with the induction of eosinophilic inflammation (al Ghamdi et al, 1997;Ayers et al, 2011;Bhakta and Woodruff, 2011). In our study, similarly to POSTN, we found that the IL-13 expression level was markedly higher in the NP tissues compared with the adjacent mucosa.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, the proportion of CD4 ' CCR8' T-cells reflecting Th2 cells is higher in rhinitis when compared to controls (42). Moreover, this observation could be confirmed in the nasal mucosa tissue of allergic fungal rhinosinusitis patients (39).…”
Section: Nasal Mucosa Dendritic Cell Type and Quantificationsupporting
confidence: 52%
“…Moreover, an active role for pDCs in allergic inflammation was also confirmed in allergen challenge studies with an important role for the DC stimulation of TNFa (38). Elevated numbers of DCs (CD209 DC-Sign) were observed in allergic fungal rhinosinusitis (39). Models of AR showed an elevated number of DCs (CD11c-positive cells with a dendritic morphology) (4,40,41).…”
Section: Nasal Mucosa Dendritic Cell Type and Quantificationmentioning
confidence: 82%
“…[533][534][535] In support of this hypothesis in CRSwNP, polyps exhibit large numbers of type 2 ILCs 536, 537 and dendritic cells. 538,539 The critical upstream epithelial cytokine is not completely clear, but high levels of TSLP activity have been identified in polyp homogenates. 540,541 Some evidence suggests that IL-33 may play a role as well, but these studies have yet to demonstrate increased expression of this cytokine at the protein level in NP tissue.…”
Section: Discussionmentioning
confidence: 99%
“…1094 NPs contain elevated levels of dendritic cells, mast cells, eosinophils, and Th2 cytokines. 538,1079,1080,1094,1097,1098 AFRS mucosa has a predominance of CD8+ T cells vs CRSwNP mucosa, which has elevated CD20+ B-cells. 1086 Various studies demonstrate elevation of fungal and nonfungal IgE within AFRS mucosa, and local IgE correlates with sinonasal eosinophilia.…”
Section: Viiig Crswnp and Afrs: Differences In Pathophysiologymentioning
confidence: 99%